On the Restricted Projective Dimension of Complexes - Li Liang; Dejun Wu (Український математичний журнал, 2013)
We study the restricted projective dimension of complexes and give some new characterizations of the restricted projective dimension. In particular, it is shown that the restricted projective dimension can be computed in terms of the so-called restricted projective resolutions. As applications, we get some results on the behavior of the restricted projective dimension under the change of rings. Вивчається обмежена проективна розмірність комплексів. Наведено дєякі нові властивості обмеженої проективної розмірності. Зокрема, показано, що обмежену проективну розмірність можна обчислити через так звані обмежені проективні резольвенти. Як застосування отримано деякі результати про поведінку обмеженої проективної розмірності при зміні кілець.